Relationship between the Nordic hamstring strength test and isokinetic hamstring strength test at different eccentric contraction velocities - Pus, K.; Hadzic, V.; Darjan, S. (International Journal of Performance Analysis in Sport, 2024)
The main purpose of the study was to analyse the relationship between the Nordic hamstring (NH) and the gold standard isokinetic eccentric strength measurements at three different eccentric velocities (30°, 60°, and 90°/s). Twenty-seven (15 male, 12 female) physical education students, experienced in strength training, performed isokinetic and NH tests. The results of the isokinetic hamstring strength test were statistically significantly higher compared to the results of the NH test, regardless of the velocity of the isokinetic test. The correlations observed ranged from moderate to large (0.419 = r = 0.582) and were statistically significant for the left leg, right leg, and the average results between the legs. However, no statistically significant correlations were found between the measures for inter-leg symmetry variables. We observed excellent intra-session reliability of the NH test results (ICC2.1 = 0.891-920), but only good reliability (ICC2.1 = 0.601) for the intra-leg symmetry variable. Although NH strength measurements were found to be highly reliable, sports practitioners should be aware of the discrepancy between the measures and interpret the results carefully. Eccentric hamstring strength and inter-leg symmetry cannot be evaluated interchangeably with the NH test and gold standard isokinetic test performed in the 90° hip flexion position.